‘A Child of Peace’ (Luke 10.6) in First Century Context - Klassen, William (New Testament studies, 1981)
The topic of peace has received critical historical scrutiny from the standpoint of the Ancient Orient and the Old Testament and sketchy treatment with reference to the Greek world. There is, however, no comprehensive study which portrays the differentiated nuances of the topic in the various schools of thought in the ancient world preceding the first century. More studies do exist on the topic of war and it is clear that a balanced picture must include the strenuous attempts made by people of many persuasions to define peace and to find a way in which humans can live at peace with each other.